Determinants of Dividend Policy in China: Evidence from Food and Beverage Sector, as well as Electronic and Equipment Sector - QUAN, QIUYI (2017)
Dividend policy is a crucial but controversial research subject in the area of corporate finance. However, very few researches have been done in emerging markets, particularly in China. Hence, this paper seeks to explore the main determinants of dividend policy among Chinese listed companies, with a focus on the food and beverage sector, as well as the electronic and equipment sector. This study applies panel data regression, covering the period between 2007 and 2016. For electronic and equipment companies, this study finds that the size of firm, corporate effective income tax, liquidity position, and growth opportunities are the determinants of dividend policy. In contrast, profitability is insignificant but negatively related to dividend policy; moreover, financial leverage is also insignificant but positively associated with dividend policy. For food and beverage companies, this paper finds that corporate effective income tax and financial leverage are the determinant factors of dividend policy, whereas the size of the firm, profitability, and liquidity have an insignificant, but positive, relationship with dividend policy. Growth opportunities have an insignificant, but negative, association with dividend policy.